Dealing with the Tough Stuff : Practical Solutions for School Administrators. - Gabriel, John (John Wiley & Sons, 2012)
The much-needed leadership tips and tools for new school administrators Fledgling school administrators are often ill-prepared for their new leadership role and are frequently left to their own devices to navigate the slippery terrain of school administration. What They Didn't Tell Me About Being a School Leader addresses some of the thornier aspects of being an assistant principal such as handling discipline, mediating student conflicts, working with parents, facilitating parent conferences, and working with staff members. This handy guide will teach the tricks of the trade in.